Multibeam bathymetry processed data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV POLARSTERN during cruise ARK-XIX/3b (PS64), Norwegian Sea, Arctic Ocean - Beyer, Andreas; Rathlau, Rike; Schenke, Hans Werner; Dreutter, Simon; Dorschel, Boris (PANGAEA, 2025)
Multibeam data were collected during RV Polarstern cruise ARK-XIX/3b (2003-06-26 to 2003-07-16). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 2 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction by cross fan calibration and with SV data from CTDs, tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.
Keywords: Arctic Ocean; Bathymetry; Hydrosweep DS2; Multibeam; Norwegian Sea; Polarstern